Identifying priority medicines policy issues for New Zealand: a general inductive study. Issue 5 (28th May 2014) - Babar, Zaheer-Ud-Din; Francis, Susan
Abstract : Objectives: To identify priority medicines policy issues for New Zealand. Setting: Stakeholders from a broad range of healthcare and policy institutions including primary, secondary and tertiary care. Participants: Exploratory, semistructured interviews were conducted with 20 stakeholders throughout New Zealand. Primary and secondary outcome measures: The interviews were digitally recorded, transcribed and coded into INVIVO 10, then compared and grouped for similarity of theme. Perceptions, experiences and opinions regarding New Zealand's medicines policy issues were recorded. Results: A large proportion of stakeholders appeared to be unaware of New Zealand's (NZ) medicines policy. In general, the policy was considered to offer consistency to guide decision-making. In the context of Pharmaceutical Management Agency's (PHARMAC's) fixed budget for procuring and subsidising medicines, there was reasonable satisfaction with the range of medicines available—rare disorder medicines being the clear exception. Concerns raised were by whom and how decisions are made and whether desired health outcomes are being measured. Other concerns included inconsistencies in evidence and across health technologies. Despite attempts to improve the situation, lower socioeconomic groups (including rural residents) Māori and Pacific ethnicities and people with rare disorders face challenges with regards to accessing medicines. Other barriers include, convenience to and affordability of prescribers and the increase of prescription fees from NZ$3 to NZ$5. Concerns related to the PHARMAC of New Zealand included: a constraining budget; non-transparency of in-house analysis; lack of consistency in recommendations between the Pharmacology and Therapeutics Advisory Committee. Constraints and inefficiencies also exist in the submission process to access high-cost medicines. Conclusions: The results suggest reasonable satisfaction with the availability of subsidised medicines. However, some of the major challenges include access to medicines in vulnerable groups, increasing costs and demand for new medicines, access to prescribers, budgetary constraints, cultural and health literacy, patient affordability and evidence requirement for gaining subsidy for medicines.